The influence of preanalytical conditions on the DJ-1 concentration in human cerebrospinal fluid. (March 2014) - Salvesen, Lisette; Tanassi, Julia T; Bech, Sara; Pålhagen, Sven; Svenningsson, Per; Heegaard, Niels HH; Winge, Kristian
Aim: The purpose of this study was to establish the influence of centrifugation and protease activity on the cerebrospinal fluid (CSF) concentrations of DJ-1 and hemoglobin.Materials & methods: The concentrations of DJ-1 and hemoglobin were determined in 12 (DJ-1) and six (hemoglobin) pairs of CSF samples, with one sample being stored without centrifugation and the other being centrifuged at 2000 × g before storage. The DJ-1 concentration was also determined in centrifuged and uncentrifuged CSF containing protease inhibitors and compared with values determined in centrifuged and uncentrifuged CSF samples without protease inhibitors. Furthermore, specific protein concentrations were determined in CSF from two groups, each comprising 23 patients with Parkinson's disease. In one group the CSF was centrifuged at 1300−1800 × g, 4°C, 10 min, and in the other at 2000 × g, 4°C, 10 min.Results: Centrifugation at 2000 × g resulted in significantly lower CSF DJ-1 concentrations compared with no centrifugation and centrifugation at a lower g-force. There was a significant difference in the hemoglobin concentration between centrifuged and uncentrifuged CSF. In all centrifuged samples the hemoglobin concentration was <200 ng/ml including blood contaminated samples centrifuged at 2000 × g. When a protease inhibitor cocktail was added to the CSF prior to centrifugation, the DJ-1 concentration was significantly higher.Conclusion: Preanalytical factors such as centrifugation and protease inhibition must be carefully controlled when handling CSF for analysis of DJ-1 and other biomarkers, as DJ-1 was influenced by blood contamination, centrifugation and protease activity.